Advancing timber construction: historical growth, research frontiers, and time series forecasting - Harrison Huang; Shan Su; Lu Li (Journal of Asian Architecture and Building Engineering, 2025)
Lauded for its capacity to curtail building energy consumption and enhance environmental performance compared to traditional mineral-based materials, wood has gained substantial traction in the construction sector. Timber construction, which is a focal point of growing interest in both industry and academia, warrants a reassessment of its historical trajectory and future prospects. This study examines publications on timber construction from 1990 to 2022 to analyze the growth path, shifting hotspots, and potential research directions in this field. By employing scientometric analysis, influential journals, articles, countries, and keywords are identified. Integration into a logistic growth model (LGM) showcases publication trends, while the Prophet model forecasts global growth. Research frontiers and emerging themes are revealed through keyword bursts surge evolution. This study offers a visualized knowledge framework, bridging current research with future trends and enabling practitioners and researchers to comprehensively grasp the evolution of timber construction.